Menuju Dewasa Yang Produktif Dan Berkarakter: Upaya Orang Tua Dalam Membina Karakter Anak Pada Usia Remaja Awal - Delmi, Tini Gustriani; Hijratunnisak, Maya; Ritonga, Supardi (STAIN Bengkalis, 2024)
Viewed from the behavioral aspect, adolescence is an age where there will be many rapid changes, especially early adolescence. This age is the beginning of the child towards adulthood, so the child is still counted as very labile in solving every problem that occurs at his age. So that the role of parents is needed significantly in fostering children in early adolescence so that later children are able to become productive and characterful adults. The method used in this research is a literature review (library research) by collecting reference sources related to the title of the study. From this study, it can be concluded that there are several important roles that become parents' efforts in educating children in early adolescence, namely by being a good role model to children, rewarding achievements and giving appropriate punishment if children make mistakes, communicating well openly and applying good habits in the family environment. Keywords: parents, character, early adolescence